Preparation of a multifunctional P-CF@Mn3O4 composite as a structural anode material. (10th August 2021) - Han, Qigang; Sheng, Yalan; Zhang, Xu
Abstract : The novel CF@Mn3 O4 composite prepared in three steps displays considerable electrochemical characteristics and potential in the flexible vehicle. Abstract : The new energy industry has increasingly higher requirements for the lightweight design and functional integration of the power energy system. As an effective solution to achieve this demand, a structural energy storage integrated composite was prepared that consists of a functional body with an ideal specific capacity combined with considerable mechanical properties. In this study, we prepared a CF@Mn3 O4 composite by compounding polyacrylonitrile (PAN)-based carbon fiber (CF) with Mn3 O4 through the three-step method of acid leaching activation, hydrothermal stirring, and high temperature annealing. As a result, the CF@Mn3 O4 composite maintains a specific capacity of 610.5 mA h g −1 after 150 cycles at the current density of 100 mA g −1, which is approximately 2.48 times higher than that of the carbon fiber. The tensile strength, Young's modulus, and elongation of the CF@Mn3 O4 composite reached 92.1%, 94.5%, and 93.5% of the original carbon fiber. These significant mechanical and electrochemical characteristics can be attributed to the synergistic effect of the carbon fiber substrate and Mn3 O4 . The carbon fiber served as a buffer substrate to relieve the volume expansion of the deposited layer during the charging and discharging processes, and the Mn3 O4 was used as a coating layer to provide more insertion sites for lithium ions, which enables a higher charge–discharge specific capacity.